Electrochemical Removal of Copper Ions Using Coconut Shell Activated Carbon - Nur Azza Azyan Muin; Hawaiah Imam Maarof; Nur Alwani Ali Bashah; Nor Aida Zubir; Rasyidah Alrozi; Norhaslinda Nasuha (Universitas Gadjah Mada, 2020)
In this work, coconut shell activated carbon (CSAC) electrode was evaluated to remove copper ion via electrochemical processes. CSAC electrode and graphite were applied as the cathode and the anode, respectively. The reusability of the electrode, the effects of initial pH, applied voltage and initial concentration were studied. The electrochemical process was carried out for 3 h of treatment time, and the electrodes (anode and cathode) were separated by 1 cm. The results revealed that CSAC is proven as a reusable electrode to remove copper ion, up to 99% of removal efficiency from an initial concentration of 50 ppm after it had been used three times. From the observation, the removal efficiency was optimum at an initial pH of 4.33 (without any initial pH adjustment). The applied voltage at 8 V showed a higher removal efficiency of copper ion compared to at 5 V.